Comparison of Quadriceps Muscle Girth Using Ultrasound Imaging In Supervised vs Unsupervised Post Operative ACL Reconstruction (Medico Legal Update, 2020)
Injury to the anterior cruciate ligament (ACL) is one of the most common knee ligament injuries. The ACLinjury is a sprain or tear of the anterior ligament (ACL). Effective exercises will reduce the risk of ACLinjury. An ACL injury in athletes is a higher incidence than other general public, such as soccer, basketball,hockey, etc. The aim of this studywas to compare the effectiveness, recovery rate and variance in bothknee-affected and non-affected muscle girth readings in supervised v/s unsupervised patient groups after thepatient underwent ACL reconstruction surgery. The participants were divided into two groups(A-Supervisedand B-Unsupervised) through a random sampling. The supervised exercise in group A performed accordingto the WILK protocol at RML hospital and un-superviseed group B performed the same WILK protocol athome. The ultrasound scans were performed after 2-4 weeks and 12-14 weeks post operation to measurethe muscle girth in both the groups. The study findings indicated the significant difference in recovery rateas well as the difference in between supervisedv/s unsupervised groups i.e. the difference of affected andunaffected knees based on ultrasound imaging was higher in un-supervised group compared to supervisedgroup (a difference of 2.3 mm in post-operation muscle girth after 12-14 weeks). The ultrasound readingof the muscle girth after 2-4 weeks post-operation showed a decline in the recovery of the muscle girth inboth the groups (9% and 8% for supervised and un-supervised groups respectively). This reduction in themuscle girth value as compared to the pre-operative values was due to arthroscopic effect, which showedthere was a transient deactivation of the muscle take place due to surgery. The ultrasound reading of themuscle girth after 12-14 weeks post-operation showed a different progressive recovery of the muscle girth inboth the groups as 31% and 10% for supervised and un-supervised groups respectively .We concluded thatsupervised exercises was better than unsupervised exercises for the early recovery after ACL recontraction.